2022
DOI: 10.3390/jcm11061517
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis-Related Knowledge and Its Relationship with Oral Health Behavior among Adult Patients Seeking Professional Periodontal Care

Abstract: Background: Periodontitis is a chronic inflammatory disease that not only damages the stomatognathic system, but may also adversely influence other systems and organs. Patients with low oral health literacy levels are more prone to gingivitis/periodontitis and have a more severe disease course. Methods: A written questionnaire was carried out to assess the knowledge of patients of the Outpatient Clinic of Department of Periodontal and Oral Mucosa Diseases, Medical University of Bialystok, Poland. The questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Additionally, individuals experiencing bleeding gums exhibited statistically lower oral health knowledge (p = 0.032). This concern was already emphasized in a study conducted among periodontal patients, confirming that low oral health literacy is closely linked to the development of gingivitis and periodontitis, with a higher likelihood of experiencing a more severe disease course [40]. Additional studies have documented a higher incidence of self-reported issues with gingival bleeding, with examples including over half of the participants in Polish [16] and South American studies [43].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Additionally, individuals experiencing bleeding gums exhibited statistically lower oral health knowledge (p = 0.032). This concern was already emphasized in a study conducted among periodontal patients, confirming that low oral health literacy is closely linked to the development of gingivitis and periodontitis, with a higher likelihood of experiencing a more severe disease course [40]. Additional studies have documented a higher incidence of self-reported issues with gingival bleeding, with examples including over half of the participants in Polish [16] and South American studies [43].…”
Section: Discussionmentioning
confidence: 82%
“…This discovery aligns with analogous outcomes found in studies conducted among student populations in Split-Dalmatia County, Croatia, and among water polo players [ 19 , 39 ]. Furthermore, parallels can be drawn with a comparative study involving adolescents from Portugal, Sweden, and Romania [ 33 ], as well as a study involving Polish patients with periodontitis [ 40 ]. In addition, slightly more than half of the respondents were aware of the preventive role of fluoride in dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Kết quả này cao hơn so với nghiên cứu của tác giả Marzieh Mohammadi-Moghaddam với 44,8% là nữ và 55,2% là nam [4]. Sự phân bố nhóm tuổi cao hơn ở nhóm tuổi trên 60 tuổi (60,5%) so với tác giả Ewa Doli´nska, với nhóm 61-70 (17%) và 71-80 (7%) [5]. Điều này có thể giải thích do đối tượng đến khám và điều trị tại Bệnh viện TƯQĐ 108 phần lớn là nhóm tuổi trên 60, chủ yếu là đối tượng bảo hiểm y tế; còn nhóm dưới 25 vẫn chiếm tỉ lệ ít nhất do ở độ tuổi này bệnh lý viêm quanh răng chưa tiến triển như ở người lớn tuổi, ở nhóm bệnh nhân trên 60 tuổi thường có kết hợp cùng các bệnh lý như đái tháo đường type II, tăng huyết áp, bệnh thận mạn tính… đều là các yếu tố nguy cơ dẫn tới trầm trọng thêm bệnh lý viêm quanh răng.…”
Section: đặC đIểm Chung Của đốI Tượng Nghiên Cứuunclassified
“…The Severe forms of periodontitis described to affect 10% of the adult population worldwide. The high rate of periodontal disease increases with age and rises rapidly in people aged 50-60 years [5]. Generally, chronic periodontitis is a progressive disease affecting gingival, periodontal ligament and alveolar bone results when gingival in ammation subsequently affects the supporting apparatus of the tooth structure [6].…”
Section: Introductionmentioning
confidence: 99%